2010
DOI: 10.1038/hr.2010.134
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among adiponectin gene polymorphisms, proteinuria and increased blood pressure in the context of placental diseases

Abstract: The etiology and pathogenesis of preeclampsia remain unclear. Little is known about the possible impact of adiponectin gene polymorphisms on the pathogenesis of preeclampsia. In this study, we analyzed the association of two adiponectin singlenucleotide polymorphisms (SNPs) with preeclampsia. One hundred eighty-eight Han Chinese pregnant women were enrolled (81 normal-term, 20 mild preeclampsia and 87 severe cases). Serum adiponectin level, and adiponectin exon 2 SNP +45T/G (rs2241766) genotype and intron 2 SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Adiponectin gene polymorphisms have been associated with hypertension and proteinuria, the clinical manifestations of preeclampsia [123]. Adiponectin gene polymorphisms have been associated with hypertension and proteinuria, the clinical manifestations of preeclampsia [123].…”
Section: Role Of Adiponectinmentioning
confidence: 99%
“…Adiponectin gene polymorphisms have been associated with hypertension and proteinuria, the clinical manifestations of preeclampsia [123]. Adiponectin gene polymorphisms have been associated with hypertension and proteinuria, the clinical manifestations of preeclampsia [123].…”
Section: Role Of Adiponectinmentioning
confidence: 99%
“…Antonio Petrone et al [27] showed the ?45G carriers had higher fasting and 2-hour glucose levels (p = 0.01 for both) and lower adiponectin levels (p = 0.02). Many studies stated the reduced circulating adiponectin levels when ?45T/G and/or ?276G/T are present in AdipoQ gene [28,29] and higher levels of circulating adiponectin are associated with a lower risk of type 2 diabetes, independently of intraabdominal fat deposition, and that adiponectin may confer a benefit in both persons with and without insulin resistance [30].…”
Section: Discussionmentioning
confidence: 99%
“…The coding sequences of ADIPOQ contain 1273 validated single nucleotide polymorphisms (http://www.ncbi.nlm.nih.gov/gene/). In ADIPOQ , two polymorphisms, T45G (rs2241766) in the 2 nd exon and G276T (rs1501299) in the 2 nd intron, have been widely investigated in association with hypertension risk and circulating adiponectin changes [10, 11]. However, the results are not often repeatable.…”
Section: Introductionmentioning
confidence: 99%